2015
DOI: 10.1016/j.jacc.2014.11.047
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Classic and Paradoxical Low Flow on Survival After Aortic Valve Replacement for Severe Aortic Stenosis

Abstract: Patients with LEF or PLF AS have a higher operative risk, but pre-operative risk score accounted only for LEF and lower LVEF. Patients with LEF had the worst survival outcome, whereas patients with PLF and normal flow had similar survival rates after AVR. As a major predictor of perioperative mortality, SVi should be integrated in AS patients' pre-operative evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
53
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 26 publications
5
53
1
3
Order By: Relevance
“…This phenotype is often misleading for clinicians because establishing the diagnosis can be challenging and the prognosis falsely reassuring given a heart that is not dilated or hypokinetic (to the contrary, the LV often appears hyperdynamic). However, studies have convincingly shown, and our data reaffirm, that paradoxical low‐gradient AS constitutes a particularly high‐risk group with operative risk of 6% to 33% and medically treated survival <50% at 3 years 27, 28, 29, 30. Patients with paradoxical low‐gradient AS are particularly vulnerable to the deleterious effects of patient‐prosthesis mismatch and, accordingly, may be good candidates for TAVR.…”
Section: Discussionsupporting
confidence: 74%
“…This phenotype is often misleading for clinicians because establishing the diagnosis can be challenging and the prognosis falsely reassuring given a heart that is not dilated or hypokinetic (to the contrary, the LV often appears hyperdynamic). However, studies have convincingly shown, and our data reaffirm, that paradoxical low‐gradient AS constitutes a particularly high‐risk group with operative risk of 6% to 33% and medically treated survival <50% at 3 years 27, 28, 29, 30. Patients with paradoxical low‐gradient AS are particularly vulnerable to the deleterious effects of patient‐prosthesis mismatch and, accordingly, may be good candidates for TAVR.…”
Section: Discussionsupporting
confidence: 74%
“…Delay of aortic valve replacement in these patients worsens their outcome32; however, the group's operative risk is increased 33…”
Section: Discussionmentioning
confidence: 99%
“…6 Severity of coexisting coronary artery disease was associated with impaired clinical outcomes at 1 year after TAVR in 445 patients with severe AS (mean age, 82.5 years; 56% female). 7 Severe AS and left ventricular ejection fraction of <50% with or without aortic valve replacement, 8,9 low-flow, low-gradient AS with reduced stroke volume index, [10][11][12][13] and reduced global longitudinal strain by speckle-tracking echocardiography 14 have increased risk of mortality after sAVR or TAVR in patients with severe AS. Midwall myocardial fibrosis that can be detected by late gadolinium enhancement, 15 and prosthesispatient mismatch 16,17 have also been reported as prognosticators in patients with severe AS after sAVR or TAVR.…”
Section: See Article By Treibel Et Almentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17] The coexistence of wtATTR and severe AS may cause severe hypertrophy and left ventricular functional impairment, which can be misdiagnosed as low-flow, low-gradient severe AS. [10][11][12][13] Recent studies have suggested that patients with wtATTR are characterized by lower left ventricular ejection fraction, stroke volume index, left ventricular basal, and midradial strains compared with age and wall thickness matched mutant ATTR patients. 18 These finding may be helpful in distinguishing wtATTR cardiac amyloidosis from patients with other causes of left ventricular hypertrophy.…”
Section: See Article By Treibel Et Almentioning
confidence: 99%